2022
DOI: 10.1021/acssuschemeng.1c07886
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic–Hydrophobic Bulky Units Modified Anion Exchange Membranes for Fuel Cell Application

Abstract: The hydroxide conductivity and alkaline stability play a significant role in the application of an anion exchange membranes (AEMs) fuel cell. These high performances are closely related to the structure of the polymer. Side-chain structure is commonly used to construct microphase separation. On this basis, a new strategy is to incorporate a rigid bulky structure into an AEM to break chain packing and reduce resistance against hydroxide ion transport. In this work, rigid bulky hydrophilic–hydrophobic side-chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…47,54 With respect to QP(SBP/Aryl)-x membranes, besides the water solvation to hydroxide ions, the steric hindrance effect from the bulky rigid spirobiindane units in the polymer framework might weaken the interaction between cationic groups and hydroxide ions and provide the protection to cationic groups. 35 As a result, all the QP(SBP/Aryl)-x membranes exhibit high tolerance to hot alkaline solutions compared to their contrast membranes. However, the QP(SBP/DP)-23 membrane having more SBP but with a higher water uptake of 118.5% at 80 °C exhibits lower alkaline stability than the QP(SBP/BP)-20 membrane having a water uptake of 97.1%.…”
Section: Ion Conductivitymentioning
confidence: 99%
“…47,54 With respect to QP(SBP/Aryl)-x membranes, besides the water solvation to hydroxide ions, the steric hindrance effect from the bulky rigid spirobiindane units in the polymer framework might weaken the interaction between cationic groups and hydroxide ions and provide the protection to cationic groups. 35 As a result, all the QP(SBP/Aryl)-x membranes exhibit high tolerance to hot alkaline solutions compared to their contrast membranes. However, the QP(SBP/DP)-23 membrane having more SBP but with a higher water uptake of 118.5% at 80 °C exhibits lower alkaline stability than the QP(SBP/BP)-20 membrane having a water uptake of 97.1%.…”
Section: Ion Conductivitymentioning
confidence: 99%
“…According to its charge, the ion exchange membrane is classified as an anion exchange membrane (AEM) or cation exchange membrane (CEM). , Herein, the research focused on AEMs for acid recovery by DD. The AEM consists mainly of a polymer backbone and ion exchange functional groups. , The polymer backbone of the AEM can be divided into two categories: hydrophobic and hydrophilic. , Hydrophobic polymers mainly include poly­(arylene ether sulfone)­s (PAESs), poly­(vinylidene fluoride) (PVDF), poly­(2,6-dimethyl-1,4-phenylene oxide) (PPO), poly epichlorohydrin (PECH), poly­(ether ether ketone) (PEEK), and polysufone (PSF) …”
Section: Introductionmentioning
confidence: 99%
“…13,14 The polymer backbone of the AEM can be divided into two categories: hydrophobic and hydrophilic. 15,16 Hydrophobic polymers mainly include poly(arylene ether sulfone)s (PAESs), 17 poly(vinylidene fluoride) (PVDF), 18 poly(2,6-dimethyl-1,4-phenylene oxide) (PPO), 19−21 poly epichlorohydrin (PECH), 22 poly(ether ether ketone) (PEEK), 23 and polysufone (PSF). 24 These polymer backbones can improve the strength and stability of the membrane, and hence, many state-of-the-art AEMs use the hydrophobic polymer backbones.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, Zhu and co-workers grafted comblike long alkyl chains to chloromethylated SEBS (CMSEBS) via the Menshutkin reaction and found that the introduction of the comblike structure improved the solubility of the polymer and effectively avoided the gelation phenomenon. At the same time, the introduction of hydrophobic alkyl chains also effectively helped construct a hydrophilic–hydrophobic microphase separation structure. …”
Section: Introductionmentioning
confidence: 99%